SOCIAL ACTIVITY CARD FOR SOCIAL SKILLS OF AUTISM SPECTRUM DISORDER (ASD): META-ANALYSIS AND NEED ASSESSMENT STUDY - Rizki Husadani; Dian Atnantomi Wiliyanto; Sinar Perdana Putra (Pusat Studi Difabilitas (PSD) LPPM Universitas Sebelas Maret, 2026)
Children with Autism Spectrum Disorder (ASD) can experience serious deficits in their social interactions due to their limited social skills. This study aims to conduct a literature review on the effectiveness of social activity cards for social skills and the field's needs for using social activity cards for individuals with ASD who experience social skill problems. The research methods included a meta-analysis (n = 20 articles) and a needs assessment (n = 23). The results of the meta-analysis indicate that the use of social activity cards has a fairly strong influence, making it effective in improving the social skills of autistic children. In the study of the analysis of the needs of social activity cards to improve the social skills of children with ASD in a special school, teachers, as many as 23 respondents, showed that the majority of respondents agreed as much as 58.52% (f = 13) and strongly agreed as much as 34.78% (f = 8). This means there is a need for and a positive response to social activity card media to improve the social skills of children with ASD among Special School teachers.